2018
DOI: 10.2196/preprints.12053
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Can Smartphone Apps Increase Physical Activity? Systematic Review and Meta-Analysis (Preprint)

Abstract: BACKGROUND Smartphone apps are a promising tool for delivering accessible and appealing physical activity interventions. Given the large growth of research in this field, there are now enough studies using the “gold standard” of experimental design—the randomized controlled trial design—and employing objective measurements of physical activity, to support a meta-analysis of these scientifically rigorous studies. OBJEC… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…Secondly, the results revealed that the total number of games played was negatively associated with the intervention effect, suggesting that shorter interventions could be more beneficial for behavior change. These results are in line with previous research [20,52] suggesting that digital interventions shorter than 3 months tend to yield greater benefits. It also suggests a « dose-response » relationship in inverted U shape, with an optimal "middle" to find.…”
Section: Discussionsupporting
confidence: 92%
“…Secondly, the results revealed that the total number of games played was negatively associated with the intervention effect, suggesting that shorter interventions could be more beneficial for behavior change. These results are in line with previous research [20,52] suggesting that digital interventions shorter than 3 months tend to yield greater benefits. It also suggests a « dose-response » relationship in inverted U shape, with an optimal "middle" to find.…”
Section: Discussionsupporting
confidence: 92%
“…The effect was less pronounced when these were combined with dietary interventions. 7 Smartphone apps have also shown good performance in weight control and obesity prevention programs. A meta-analysis of 12 studies on adolescents and adults showed significant reduction in weight (−1.07 kg, 95% confidence interval [CI]: −1.92 to −0.21) and body mass index (−0.45 kg/m 2 , 95% CI: −0.78 to −0.12) with the use of mobile apps; however, with nonsignificant effect on increase in physical exercise.…”
Section: Ehealth Interventionsmentioning
confidence: 99%
“…Previous literature reviews provide evidence of promising results of smartphone applications for promoting PA behavior [21,22,23,24,25]. Evidence from nonrandomized controlled trials found that smartphone apps could either increase PA, decrease PA, or prevent PA decline [21].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from nonrandomized controlled trials found that smartphone apps could either increase PA, decrease PA, or prevent PA decline [21]. Romeo et al [25] conducted a subgroup analysis on healthy adult across all ages that resulted in a small, inconclusive and high heterogeneous result (mean difference= +649,54 steps per day, 95% CI -822.66 to 21221.74, I 2 80%). Heterogeneous and inconclusive results from previous systematic reviews could be attributable, in part, to various population.…”
Section: Introductionmentioning
confidence: 99%